OPTIMIZED MANAGEMENT STRATEGY FOR CONSTRUCTION PROJECTS CONSIDERING THE TRADE-OFF OF ESTIMATE SCHEDULE AND COST AT COMPLETION - Liem Stefani Meilia Gunawan; Min-Yuan Cheng; Doddy Prayogo (Program Studi Magister Teknik Sipil - Petra Christian University, 2019)
Nowadays, the minimization of project time and cost is an important issue. However, time and cost problems are difficult to solve. They are affected by the uncertain factor. Then, the construction project always fails to achieve the effectiveness of time and cost performance. It causes delays and cost overrun. In this research, SOS-NN-LSTM is required to establish the estimate schedule to completion (ESTC) and estimate cost to completion (ECTC) prediction model based on time now performance. Then, the prediction model will be integrated with MOSOS to obtain the optimal prediction value. The integration is needed because there is no direct equation to calculate the ESTC and ECTC. The Pareto curve identified based on the prediction values of MOSOS. The Pareto curve is used to determine the optimal trade-off between project duration and project cost. Then, the indifference curve is used to solve the trade-off problem between estimate schedule at completion (ESAC) dan estimate cost at completion (ECAC) which give the decision-maker preference.